On fixing the magnitudes of gravitational constant and strong coupling constant - UV, Satya Seshavatharam; S, Lakshminarayana (International Journal of Advanced Astronomy, 2015)
In the earlier published papers the authors suggested that, â€œMagnitude of the unified force can be assumed to be equal to the classical or astrophysical force limit . Strength of any interaction can be defined as the ratio of the operating force magnitude and the magnitude of . If strength of the Schwarzschild interaction is assumed to be unity, then weak interaction strength seems to be â€˜squared Avogadro numberâ€™ times less than the Schwarzschild interaction. The characteristic atomic force can be represented by â€. Thinking in this way, atomic gravitational constant can be expressed as Â With current atomic physical constants and with the assumed two new grand unified back ground numbers analytically - value of Â can be fixed for 10 digits and can be verified. Inverse of the strong coupling constant can be considered as the â€˜natural logarithm of square root of ratio of gravitational and electromagnetic force ratio of down quark mass where the operating gravitational constant is squared Avogadro number times the gravitational constantâ€™. Finally an attempt is made to fit and understand the mystery of Up and Down quarks, nuclear stability, and nuclear binding energy. For medium and heavy atomic nuclides, at the stable mass number, nuclear binding energy seems to be equal to the sum of rest energy of Â up quarks and Â down quarks.